Virulence of Brown Planthopper and Development of Core Collection of the Pest - Chaerani, Chaerani; Damayanti, Diani; Trisnaningsih, Trisnaningsih; Yuriyah, Siti; Kusumanegara, Kusumawaty; Dadang, Ahmad; Sutrisno, Sutrisno; Bahagiawati, Bahagiawati (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Brown planthopper is the most important rice pest in Indonesia. Its high adaptability to feed and reproduce on previously introduced resistant varieties to form more virulent population often causes BPH outbreak and hopperburn that lead to total crop yield loss. Rice breeding for resistant to BPH requires information on the current status of BPH virulences in the fields to anticipate the virulence adaptation on new varieties. The objectives of this study were to investigate the degree of virulence of BPH populations and to cluster the BPH virulence to form BPH core collection. Thirteen BPH populations collected from paddy fields in six provinces (Banten, West Java, Central Java, East Java, South Kalimantan, and South Sulawesi) in 2011 and 2013 were tested on 10 differential rice varieties and seven host varieties of BPH populations, using the standard seedbox screening technique. Based on resistance reaction of four differential varieties (TN1, Mudgo, ASD7, and Rathu Heenathi), most BPH populations were identified as more virulent than biotype 4 (T1, Banten, PG, West Java; BY, East Java; B2 and B3, South Kalimantan; X1 and X3, South Sulawesi), four populations were biotype 4 (JWDL, Central Java; SD, East Java; X2 and X4, South Sulawesi), and one population each was biotype 3 (T2, Banten) and biotype 2 (S1, West Java). Populations X1 and B3 showed broad virulences to all varieties, whereas T2 was the least virulent. BPH fieldâs population had evolved into more virulence than biotype 4. Genotype resistance screening should use the BPH of this virulence population. Five BPH clusters which were further divided into 10 subclusters representing differential virulence toward 10 differential varieties were present in the tested BPH. Each virulence cluster was characterized by its ability to overcome four to eight single or double resistant genes. This BPH virulence core collection can be used in the characterization studies of candidate for resistant varieties or to form near-isogenic lines, or to study the insect and rice plant interaction.